PENGGUNAAN SIMDIKLAT DALAM MENINGKATKAN MUTU KEGIATAN KEDIKLATAN DI BALAI DIKLAT KEAGAMAAN SURABAYA - Fauzi, Ahmad; Krismananda, Much. Wildan; Fuadi, Aziz (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
The use of information technology in managing education and training (training) has become a basic need. The series of training activity processes also requires the Syndiklat application. This research aims to determine the benefits of using the Simdiklat application in improving the quality of training activities held by the Surabaya Religious Education and Training Center. This research uses a qualitative approach with data mining methods through direct observation and interviews with informants. The research results show that Simdiklat is very helpful in the preparation, implementation and evaluation process as well as database storage. However, the quality of Simdiklat still needs to be improved by adjusting user needs so that the application is effective and efficient.